Exercise in Sub-zero Temperatures and Airway Health: Implications for Athletes With Special Focus on Heat-and-Moisture-Exchanging Breathing Devices - Hanstock, Helen G.; Ainegren, Mats; Stenfors, Nikolai (Frontiers in Sports and Active Living, 2020)
Asthma is highly prevalent among winter endurance athletes. This “occupational disease” of cross-country skiers, among others, was acknowledged during the 1990s, with the pathogenesis attributed to repeated and prolonged exposure to cold, dry air combined with high rates of ventilation during exercise. Nevertheless, more than 25 years later, the prevalence of asthma among Scandinavian cross-country skiers is unchanged, and prevention remains a primary concern for sports physicians. Heat-and-moisture-exchanging breathing devices (HMEs) prevent exercise-induced bronchoconstriction in subjects with pre-existing disease and may have potential as a preventative intervention for healthy athletes undertaking training and competition in winter endurance sports. Herein we firstly provide an overview of the influence of temperature and humidity on airway health and the implications for athletes training and competing in sub-zero temperatures. We thereafter describe the properties and effects of HMEs, identify gaps in current understanding, and suggest avenues for future research.